What was the ancestral sex-determining mechanism in amniote vertebrates? - Johnson Pokorná, Martina; Kratochvíl, Lukáš (Biological reviews of the Cambridge Philosophical Society, 2016)
Amniote vertebrates, the group consisting of mammals and reptiles including birds, possess various mechanisms of sex determination. Under environmental sex determination (ESD), the sex of individuals depends on the environmental conditions occurring during their development and therefore there are no sexual differences present in their genotypes. Alternatively, through the mode of genotypic sex determination (GSD), sex is determined by a sex-specific genotype, i.e. by the combination of sex chromosomes at various stages of differentiation at conception. As well as influencing sex determination, sex-specific parts of genomes may, and often do, develop specific reproductive or ecological roles in their bearers. Accordingly, an individual with a mismatch between phenotypic (gonadal) and genotypic sex, for example an individual sex-reversed by environmental effects, should have a lower fitness due to the lack of specialized, sex-specific parts of their genome. In this case, evolutionary transitions from GSD to ESD should be less likely than transitions in the opposite direction. This prediction contrasts with the view that GSD was the ancestral sex-determining mechanism for amniote vertebrates. Ancestral GSD would require several transitions from GSD to ESD associated with an independent dedifferentiation of sex chromosomes, at least in the ancestors of crocodiles, turtles, and lepidosaurs (tuataras and squamate reptiles). In this review, we argue that the alternative theory postulating ESD as ancestral in amniotes is more parsimonious and is largely concordant with the theoretical expectations and current knowledge of the phylogenetic distribution and homology of sex-determining mechanisms.
Keywords: Sex Chromosomes; Male; životní prostředí; pohlavní chromozomy; environmental sex determination; Sex Determination Processes; Environment; biologická evoluce; mužské pohlaví; polyphenism; sexual dimorphism; reptiles; Animals; sex chromosomes; Vertebrates; ženské pohlaví; Biological Evolution; zvířata; Sauropsida; sex ratio; phylogeny; procesy určující pohlaví; Female; obratlovci